The politicization of police stops in Europe: public issues and police reform - Maillard, Jacques de; Verfaillie, Kristof; Rowe, Michael (Palgrave's critical policing studies, 2024)
Chapter 1- Police stops in Europe: a citadel under siege, but still standing -- Part 1. Police stops, protest and the democratisation process -- Chapter 2 -The rise of Police stops as a public issue in twenty-first century Poland -- Chapter 3 -The issue of police stops in Croatia -- Chapter 4 - Police stops in Hungary: in the light of public debates and media coverage -- Chapter 5 - Policing migration, protest and sovereignty: the politicisation of stop & search practices in Spain -- Part 2 Ethnic profiling in European countries. -Chapter 6 - Contrôles au faciès in France: From denial to recognition to inaction -- Chapter 7- Human Rights, Criminalisation of Migrants and Racism Debates: Public Discussions about Police Stops and Ethnic Profiling in Finland -- Chapter 8 - Police identity checks in Belgium: a critical media content analysis -- Chapter 9 - Police stops in Norway: public controversies and minority status -- Part 3 - Political debates, limitation and extensions of police powers -- Chapter 10 - The power of a stooshie: Learning the lessons of stop and search in Scotland for implementing organisational change in policing -- Chapter 11 -Contextualising police stops ion public debates: policy turning points in Germany -- Chapter 12 - The Politics of “Stop & Search” in the Netherlands: a process of juridification -- Chapter 13 - Police Stop and Search Practices in Austria -- Chapter 14 - Regulating Stop-and-Search in England and Wales: public controversy as a catalyst for control.